Effect of Edible Coating of Aromatized Biopolymer on Spatial Distribution of Fat in Gel Emulsion - Ardi Manggala Putra; Husnul Hatimah; Rizki Aristyarini; Fitrawaty Orista Evar; Andriyana Gustam; Suryansyah Surahman; Nur Hardina; Prihatin Prihatin (Universitas Islam Raden Rahmat, Malang, 2025)
This study aimed to evaluate the effect of aromatized thin-layer biopolymers on sensory perception in gel emulsions with spatial distribution of fat. An edible coating technique was used with Wijsman butter and cheese-cheese aromas to enhance fat perception without compromising other sensory attributes. Homogeneous gels with 20% fat content were applied with scented and unscented thin-layer biopolymers and then analyzed using the hedonic organoleptic method involving hardness, suppleness, color (transparency), and aroma parameters. The results showed that the scented thin-film biopolymer improved panelists' acceptance of fat aroma perception (score of 7.8), compared to the unscented biopolymer (score of 5.5). Panelists' acceptance of hardness, suppleness, and gel transparency did not differ significantly between the flavored and unscented treatments (values ranged from 7.1 to 7.9). This suggests that the addition of aroma can improve the perception of fat without affecting the physical quality of the gel. The use of aromatized thin-layer biopolymers can be an effective strategy to improve the sensory quality of low-fat food products, which is relevant in efforts to address the prevalence of overnutrition. This study contributes to the development of healthy food technology while maintaining consumer preferences for product texture and visuals.